Editorial - KHOURY, Elie (International Arab Journal of Dentistry (IAJD), 2022)
“Social media don’t teach us to dialogue because it is so easy to avoid controversy… most people use social media to cut themselves a comfort zone where the only sounds they hear are the echoes of their own voice, where the only things they see are the reflections of their own face…” As we know, global access to the Internet became possible at the end of the 1990s. By 2010, more then 80% of the planet population is using Internet. Such an increase has resulted due to the development of social media and on line networks, a phenomenon of communication that has important behavioral, economic and political repercussions...